Effects of lindane and carbaryl on insects, soil and plant nitrogen, and grain yield of rice - De Datta, S.K.; Ayyangar, R.S.; Magbanua, J.T. (Cambridge University Press, 1967)
Experiments were conducted during three crop seasons to determine the effects of lindane and carbary1, applied to the irrigation water or incorporated in the soil, on the control of insects, on the nitrogen status of the soil and plant, and on grain yield of lowland rice. In two crop seasons the highest grain yield was obtained from three applications of lindane to the irrigation water and carbaryl sprays at 7- to 10-day intervals, and in the third season from 20 kg/ha. carbaryl incorporated in the soil without any lindane treatment or carbaryl spray. In two seasons, soil-incorporated carbaryl at 20 kg/ha. active ingredient gave a significantly higher yield than the no-insecticide control, and in one season the increase in grain yield was just below the significant level. Most of the grain yield increase with 20 kg/ha. carbaryl incorporated into the soil was caused by better control of stem borer and leafhopper and a significant reduction in virus infection.